1989
DOI: 10.1055/s-2006-961772
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Screening of Fresh Plant Material for Glycosidic Bound Volatile Compounds1

Abstract: A modified, simple method for screening of fresh plant material for glycosidic bound volatile compounds is described. The plant material is "stabilized" in boiling water, possible occurring volatile compounds removed by hydrodistillation, the remaining aqueous extract treated with beta-glucosidase, and the volatile compounds, liberated by the enzymatic hydrolysis, isolated and analysed by gas chromatography. In MELISSA OFFICINALIS and MENTHA SPICATA relatively large amounts of glycosidic bound eugenol and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…49290, Fluka) at 28°C for 16 h and the volatile compounds were collected in n-hexane (0.5 ml) by hydrodistillation. 28 All the essential oils and the volatile fractions were analysed by GC and GC-MS.…”
Section: Isolation Proceduresmentioning
confidence: 99%
“…49290, Fluka) at 28°C for 16 h and the volatile compounds were collected in n-hexane (0.5 ml) by hydrodistillation. 28 All the essential oils and the volatile fractions were analysed by GC and GC-MS.…”
Section: Isolation Proceduresmentioning
confidence: 99%
“…The remaining aqueous extracts were treated with β-glycosidase at 28 °C for 16 h and the volatile compounds produced by enzymatic hydrolysis were collected in n-hexane (0.5 ml) by hydrodistillation. 24 All the essential oils and the volatile fractions obtained by hydrolysis were analysed by GC and GC-MS.…”
Section: Isolation Proceduresmentioning
confidence: 99%
“…The natural function of glycosidases is to hydrolyze glycosides. Hence, they have been used for the screening of glycosidically bound volatiles in fresh plant material (25,26) and to release aroma compounds (27,28). However, in 1914 Bourquelot already showed that it was possible to use -galactosidase for the reverse reaction by tuning the reaction conditions (29).…”
Section: Preparation Of Glycosidesmentioning
confidence: 99%